Amalgamation of high-κ dielectrics with graphene: A catalyst in the orbit of nanoelectronics and material sciences - Khanna, Sadhak (Frontiers in Physics, 2022)
In electronics, the size of transistors is now minimized to a few nanometers. Electronic Device’s accuracy and authenticity are facing a major problem of leakage currents. To get relief from this tricky situation, high-k dielectrics which have a huge band gap and permittivity are established to increase the capacitance and remove the leakage of currents. Three major properties are related to current flow: (a) Band gap, (b) resistance, and (c) dielectric constant. High-κ or higher dielectric constant means how much charge a material could hold. A Large band gap is needed to vanquish charge injection that causes leakage current. So, these are the insulating materials that store charges when placed in-between metallic plates. The dielectric thickness of high-κ can be enhanced without enhancing the capacitance, hence reducing the leakage current. These materials need to be functionalized. Some materials having low physical and chemical barriers are needed to be functionalized with them. The best material to be integrated with these high- κ is graphene, as a goal of large area uniformity of electrical properties is achievable with them and willingly separable graphene is also available. Here we will scrutinize the current advancement in graphene electronics-based research on high- κ dielectrics like Al₂O₃ (used as obstructing oxide in charge trap flash memory) with graphene. This article is about to review the amalgamation of oxides like high-κ dielectrics with graphene, which are necessary for the understanding of top-gated electronic devices made by graphene which includes field effect transistors and other electronic devices.